CLASSIFICATIONS OF OBSESSIVE-COMPULSIVE DISORDER IN THE XXI CENTURY - Lyamets, Artem (PSYCHOLOGICAL JOURNAL, 2019)
Obsessive-compulsive disorder is one of thought disorders (disorder of goal creation and goal implementation), which is characterized by obsessive conditions, self-chekings, rituals, which are regularly repeated. The above-mentioned phenomenon applied to «small» psychiatry and is considered to be neurosis, although OCD as the symptom can be observed in different registers of mental illnesses. The inaccuracies in determining of obsessive-compulsive disorder are visible in ICD-10, where the different varieties of OCD (F42) haven’t been formulated yet (ICD-10 does not take into account the factor of the manifestations of compulsions and obsessions in psychotic, psychopathic and vegetative registers). In different medical standards this phenomenon is reviewed mainly in the coordinate system of the proportionality of obsessions and compulsions. The above-mentioned condition of the development of that problem doesn’t allow to diagnose clearly the type of OCD, whereas reviewing of obsessive-compulsive disorder only in the format of neurosis leads to the cases, when the incurability of OCD is noted (the number of the persons, who has taken the treatment in phychiatric hospitals or centers of psychological help, continue complaining of obsessions and compulsions). The above-mentioned situation with obsessive-compulsive disorder is the consequence of the nonsimple history of the development for that concept and scientific term. In this article the different classifications of the phenomenon of OCD are being analyzed: ICD-10, DSM-IV, DSM-V and etc. The different categorial conceptions are being reviewed: proportionality of obsessions and compulsions, representations of different obsessive-compulsive syndromes, specification of classification axises, research of main and secondary disorders, etc. It has been suggested to use registered-axial classifications with specifiers for improving the standards ICD-11 and DSM-V for diagnostics of obsessive-compulsive disorder. In the conclusions the author suggested to comprehend OCD as the dependent from the registers symptom and proposed to consider the chart of registered-axial classification (with specifiers) of obsessive-compulsive disorder.